Incidence of amyotrophic lateral sclerosis in Rhineland-Palatinate, Germany. Issue 3 (1st June 2014) - Wolf, Joachim; Wöhrle, Johannes C.; Palm, Frederick; Nix, Wilfred A.; Maschke, Matthias; Safer, Anton; Becher, Heiko; Grau, Armin J.
Abstract: There is a lack of prospective and population based epidemiological data on amyotrophic lateral sclerosis in Germany to date. The ALS registry Rhineland-Palatinate was established to investigate the incidence, course and phenotypic variety of ALS in this south-west German state of about 4 million inhabitants. During the period 2010–2011, consecutive incident patients with amyotrophic lateral sclerosis according to the revised El Escorial criteria were included and followed up using multiple overlapping sources of case ascertainment. One hundred and forty-six patients were enrolled. The annual crude incidence for amyotrophic lateral sclerosis in Rhineland-Palatinate was 1.8/100, 000 person-years (95% CI 1.6–2.2). Male to female ratio was 1.1:1. Incidence increased with age reaching a peak in the 70–74 years age group and declined thereafter. Late-onset ALS (≥ 75 years) was found in 14.4% of patients. About 32% of patients presented with bulbar onset. In conclusion, incidence rate of amyotrophic lateral sclerosis in Rhineland-Palatinate is within the range of other prospective population based registers in Europe and North America. Gender ratio is nearly balanced.